Mg2Si1-xSnx, a case study of pressure effects on a thermoelectric material - Gana, Hadjer; Laggoun, Ibrahim (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2018)
In this work, we carried out a theoretical study using the augmented and linearized augmented plan wave method (FP-LAPW), based on the density functional theory (DFT) implemented in the WIEN2K code, to determine the structural and electronic properties of the compounds Mg2Si1-xSnx (x = 0.0.25,0.5, 0.75, 1) at pressure (P = 5Gpa, 10Gap, 15Gpa), thus, the calculation of transport properties by semiclassical BoltzTraP methods. Exchange potential and correlation (XC) is processed by the generalized gradient approximation (GGA) and the modified Beck Jonhson approximation (mBJ).